PENGARUH ROE DAN DER TERHADAP HARGA SAHAM PADA SEKTOR PERDAGANGAN ECERAN - Nurmala Alfiah; Lucia Ari Diyani (Politeknik Ubaya, 2017)
This study aims to test the Influence of Return on Equity (ROE) and Debt to Equity Ratio (DER) Against Stock Price. This study was taken because there is still a difference between previous researchers. The study used external secondary data, sample technique used Purposive Sampling from eight (8) companies which met the Sampling criteria existing from 23 companies. The method used is multiple linear regression analysis. The results of this study shows that Return on Equity (ROE) has no significant effect on Stock Price, while Debt to Equity Ratio (DER) has a significant effect on Stock Price. Simultaneously ROE and DER have a significant effect to the stock price that is equal to 22,5% while the rest 77,5% influenced by other factor.